2015
DOI: 10.3892/ol.2015.3093
|View full text |Cite
|
Sign up to set email alerts
|

Relative mRNA expression of prostate-derived E-twenty-six factor and E-twenty-six variant 4 transcription factors, and of uridine phosphorylase-1 and thymidine phosphorylase enzymes, in benign and malignant prostatic tissue

Abstract: Abstract. Prostate cancer is the most frequent urological tumor, and the second most common cancer diagnosed in men. Incidence and mortality are variable and appear to depend on behavioral factors and genetic predisposition. The prostate-derived E-twenty-six factor (PDEF) and E-twenty-six variant 4 (ETV4) transcription factors, and the thymidine phosphorylase (TP) and uridine phosphorylase-1 (UP-1) enzymes, are reported to be components of the pathways leading to tumorigenesis and/or metastasis in a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Of the 11 genes included in Table 5, more than half of them have been previously reported such that expression changes have been associated in prostate tissue, often with various stages of prostate cancer. The top result from the GPGE analysis, ETV4 (ETS variant 4) has been previously found in studies of prostate cancer to have significantly higher relative expression in the tumor tissues than in benign samples 79 , as well as an association with poor prognosis 80,81 . We found that increased predicted expression of ETV4 is associated with increased risk of BPH in this study (p-value = 0.0015).…”
Section: Discussionmentioning
confidence: 91%
“…Of the 11 genes included in Table 5, more than half of them have been previously reported such that expression changes have been associated in prostate tissue, often with various stages of prostate cancer. The top result from the GPGE analysis, ETV4 (ETS variant 4) has been previously found in studies of prostate cancer to have significantly higher relative expression in the tumor tissues than in benign samples 79 , as well as an association with poor prognosis 80,81 . We found that increased predicted expression of ETV4 is associated with increased risk of BPH in this study (p-value = 0.0015).…”
Section: Discussionmentioning
confidence: 91%
“…Clinically, a high level of ETV4 has been found to be associated with Gleason score, pathological tumor stage, and poor prognosis of patients with prostate cancer. 24 Furthermore, ETV4 was found to have a more increased expression in prostate cancer samples than in benign samples, 25 and it was expressed in cell nuclear extracts and cancer tissue protein lysates. 26 However, another group revealed that ETV4 upregulation was rarely found in prostate cancer (3%), and it was particularly more infrequent in higher-grade prostate cancer.…”
Section: Urological Tumorsmentioning
confidence: 99%